Pengaruh Work-Life Balance terhadap Kepuasan Kerja Dosen Wanita di Universitas Negeri Padang - Sabila, Adinda Ahda; Dwatra, Free Dirga (TSAQOFAH, 2025)
This study is motivated by the importance of achieving a balance between work demands and personal life for female lecturers, given their dual roles, which can influence job satisfaction. The research aims to analyze the impact of work-life balance on the job satisfaction of female lecturers at Universitas Negeri Padang. A quantitative method with a survey approach was employed, involving 89 female lecturers selected through purposive sampling. Data were analyzed using linear regression. The results indicate a positive and significant correlation between work-life balance and job satisfaction, with a significance value of 0.000 (p < 0.05). An R square value of 0.315 suggests that work-life balance accounts for 31.5% of the variation in job satisfaction. These findings affirm that a higher level of work-life balance increases the likelihood of achieving job satisfaction among female lecturers. The implications of this study highlight the need for institutional strategies to support the balance between professional and personal roles for female academics, in order to enhance overall performance and workplace well-being.